Bridging Gaps: Enhancing Collaboration through Boundary-Spanning Competencies in Hospital Social Work - Abdulaziz Mohammed Al-Fawzan; Saleh Mani Al-Bulaihi; Sahid Jahaz Alharbi; Fahad Faleh Battal Alrashidi; Naif Saeed Al Harbi; Majed Jazaa Al Anzi; Ghanem Yousef Abdullah Alyousef; Fatmah Rube Alenizi; Waleed Mohammed Altuwayjiri; Ghazee Suleiman Alharbi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The role of hospital social workers has evolved to encompass a broader scope of responsibilities within interprofessional healthcare teams. As boundary-spanners, hospital social workers must navigate and collaborate across various professions, organizations, and systems to deliver comprehensive and coordinated patient care. This paper explores the importance of boundary-spanning competencies in hospital social work and their impact on strengthening relationships between different parties involved in patient care. Through a qualitative thematic analysis of relevant literature, several key boundary-spanning competencies are identified, including communication and interpersonal skills, emotional intelligence and empathy, adaptability and flexibility, collaborative problem-solving and conflict resolution, knowledge of healthcare systems and community resources, advocacy and systems change, and professional identity and role clarity. The findings contribute to a deeper understanding of the essential competencies required for hospital social workers to effectively navigate interprofessional collaboration and boundary work within healthcare settings. The insights have implications for social work education and training, interprofessional collaboration and teamwork, healthcare policy and practice, and patient-centered care and community engagement. By recognizing and fostering these boundary-spanning competencies, healthcare organizations can create an environment that promotes effective collaboration, seamless care coordination, and a holistic approach to addressing the diverse needs of patients and their families.